Linguistic politeness in intercultural communication in Japanese - Suraiya Mohd. Ali (Journal of Modern Languages)
Politeness is said to be the essence of Japanese communication and is deeply rooted in its culture. Linguistic politeness is necessary for smooth communication in other cultures too. Ide (1989) defines linguistic politeness as " the language associated with smooth communication realized through (I) the speaker's use of intentional strategy to allow his or her message to be received favorably by the addressee, (2) the speaker's choice of expressions to conform to the expected and or prescribed norms of speech appropriate to the contextual situation in individual speech communities" (ibid:225).